2019
DOI: 10.3390/ijms20174183
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of VDR and Megalin in Semi-Selectivity of Side-Chain Modified 19-nor Analogs of Vitamin D

Abstract: 1,25-dihydroxyvitamin D3 (1,25D3) is implicated in many cellular functions, including cell proliferation and differentiation, thus exerting potential antitumor effects. A major limitation for therapeutic use of 1,25D3 are potent calcemic activities. Therefore, synthetic analogs of 1,25D3 for use in anticancer therapy should retain cell differentiating potential, with calcemic activity being reduced. To obtain this goal, the analogs should effectively activate transcription of genes responsible for cell differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Compared to 1,25D3, the affinity of PRI-5105 was significantly reduced while that of PRI-5106, its diastereomer, was slightly augmented. However, the decrease of VDR-binding affinity [8] did not affect the potency of PRI-5105 to induce differentiation of HL-60 cells in comparison to 1,25D3 [7,8].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Compared to 1,25D3, the affinity of PRI-5105 was significantly reduced while that of PRI-5106, its diastereomer, was slightly augmented. However, the decrease of VDR-binding affinity [8] did not affect the potency of PRI-5105 to induce differentiation of HL-60 cells in comparison to 1,25D3 [7,8].…”
Section: Introductionmentioning
confidence: 74%
“…In this study we have complemented the previously published biological profiles of these analogs [7], analyzing their anticancer potential on colorectal cancer (CRC) cell lines as well as their CYP24A1-dependent metabolism, compared to 1,25-dihydroxycholecalciferol (1,25-dihydroxyvitamin D 3 , 1,25D3) as a gold standard. The binding affinities of these analogs to VDR were already investigated in another study [8]. The results showed that the absolute configuration at C-24 in the 19-nor analogs, which have a vitamin D 2 -like side chain that is extended by one carbon (C-20a), influences the VDR affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor endocytosis can generate rapid intracellular signals via the Rab5/PI3-kinase pathway [91]. However and from knockout studies, we have excluded the involvement of megalin and cubilin as to the differentiating potency and selectivity of our analogues of 1,25D3 [92]. Even so, an interplay between genomic events and rapid intracellular signalling is likely to be important to how 1,25D3 brings about a change to the status of developing and mature haematopoietic cells.…”
Section: Unfinished Business Regarding the Action Of 125d3 On Haematmentioning
confidence: 99%
“…CYP24A1 is present in the inner mitochondrial membrane of all calcitriol responsive cells. After exposure to calcitriol, the expression of CYP24A1 increases, however, the kinetics of the increase is cell-type specific [ 11 ]. Interestingly, several tumors have a high constitutive expression of CYP24A1, which may lower the local concentration of calcitriol in the cancer microenvironment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%